Failed globalisation inequality, money, and the renaissance of the state - Flassbeck, Heiner 1950-; Steinhardt, Paul 1958- (World Scientific, 2020)
"Provides a new approach to economic development, international trade, saving, investment and debt."
Keywords: Globalisierung / (DE-627)091364108 / (DE-STW)19071-3; Digitalisierung / (DE-627)1028324774 / (DE-STW)30171-4; Handelsliberalisierung / (DE-627)091348587 / (DE-STW)19317-4; Wirtschaftsliberalismus / (DE-627)091401089 / (DE-STW)10986-6; Internationale Wirtschaftspolitik / (DE-627)091400163 / (DE-STW)10619-5; Internationale Zusammenarbeit / (DE-627)091368510 / (DE-STW)19708-3; Welt / (DE-627)09140004X / (DE-STW)16809-5; Economic development / Social aspects; Equality; International economic integration